2008
DOI: 10.1186/1471-2199-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the transcriptional activity of endogenous NFAT5 in primary cells using transgenic NFAT-luciferase reporter mice

Abstract: Background: The transcription factor NFAT5/TonEBP regulates the response of mammalian cells to hypertonicity. However, little is known about the physiopathologic tonicity thresholds that trigger its transcriptional activity in primary cells. Wilkins et al. recently developed a transgenic mouse carrying a luciferase reporter (9xNFAT-Luc) driven by a cluster of NFAT sites, that was activated by calcineurindependent NFATc proteins. Since the NFAT site of this reporter was very similar to an optimal NFAT5 site, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 47 publications
4
74
0
Order By: Relevance
“…ERK2 siRNA reduces high NaCl-dependent NFAT5 transcriptional activity in nucleus pulposus [62] and in HEK293 cells [29] . It is reasonably concluded that ERK1/2, or at least ERK2, contributes to tonicity-dependent activation of NFAT5 [30] , although it is not clear why PD98059 fails to inhibit NFAT5 transcriptional activity in the primary splenocytes [61] . The effect of JNK on tonicity-dependent activation of NFAT5 is elusive and also least studied.…”
Section: Potential Clinical Significance Of This Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…ERK2 siRNA reduces high NaCl-dependent NFAT5 transcriptional activity in nucleus pulposus [62] and in HEK293 cells [29] . It is reasonably concluded that ERK1/2, or at least ERK2, contributes to tonicity-dependent activation of NFAT5 [30] , although it is not clear why PD98059 fails to inhibit NFAT5 transcriptional activity in the primary splenocytes [61] . The effect of JNK on tonicity-dependent activation of NFAT5 is elusive and also least studied.…”
Section: Potential Clinical Significance Of This Reviewmentioning
confidence: 99%
“…Subsequent studies indicate that PKA contributes to tonicity-dependent activation of NFAT5 by suppressing the negative effect of GSK-3β on the transcription factor through increasing the inhibitory phosphorylation of GSK-3β at serine 9 [81] . PKA has also been suggested to contribute to tonicity-dependent activation of NFAT5 in the primary splenocytes, based on the inhibitory effect of H89 [61] . H89…”
Section: Mitogen-activated Protein Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the slightly hypertonic milieu of the thymus could be harmful for NFAT5-deficient thymocytes (24), but it is unclear whether thymic tonicity can activate NFAT5 (25). Nfat5 fl/fl, Lck-Cre mice had normally isotonic plasma, and their DN3, DN4, and DP thymocytes expressed normal levels of the osmostress-inducible, NFAT5-dependent genes Akr1b3 and Slc5a3 (SI Appendix, Fig.…”
Section: Nfat5 Has Different Effects On Thymocyte Proliferation and Smentioning
confidence: 99%
“…Whereas the thymocyte and T-lymphocyte deficiency of NFAT5-null mice can be explained by their systemic hypernatremia (21, 22), mice expressing a T-lymphocyte-restricted dominant negative NFAT5 transgene were shown to have reduced thymic cellularity and peripheral T lymphopenia (23). Because the tonicity of the thymus is not high enough to activate NFAT5 (21,24,25), this suggests an osmostress-independent role of NFAT5 in thymocyte development. Here we describe that NFAT5 expression is regulated by the IκB kinase β (IKKβ) pathway in thymocytes and acts as a survival factor downstream from the pre-TCR, independent of its osmoprotective function.…”
mentioning
confidence: 99%